ChemInform Abstract: Silver Trifluoromethanesulfonate and Metallic Copper Mediated Syntheses of 1, 2, 3‐Triazole‐O‐ and Triazolyl Glycoconjugates: Consecutive Glycosylation and Cyclization under One‐Pot Condition. Issue 46 (October 2016) - Dutta, Samrat; Gupta, Shyam Ji; Sen, Asish Kumar
Abstract: The title reaction involves consecutive glycosidation and azide alkyne cyclization under one‐pot conditions using a combination of AgOTf and Cu(0) catalyst.